Effectiveness of surgical degermation methods: An integrative review (Research, Society and Development, 2021)
Objective: to provoke a reflection on the knowledge of health professionals in relation to the methods of degermation. Methodology: this is an Integrative Literature Review, with a qualitative approach. Data collection took place between February and March 2021, based on articles contained in the databases indexed in the Virtual Health Library and the combination of Health Sciences Descriptors: “Antissepsia”; "Hand Disinfection" and "Hand Hygiene", in portuguese, english and spanish. The instrument for organizing the content was a table containing the authors, database, magazine of publication, type of study and year of publication. Results: 10 articles were selected from the databases: Base de Dados de Enfermagem, Literatura Latino-Americana e do Caribe em Ciências da Saúde and Medical Literature Analysis and Retrieval System On-line. Conclusion: it was found through the articles that to avoid the proliferation of microorganisms, adequate hand hygiene and regular adherence to the good practices that are recommended must be adopted. Also, it was possible to identify the dispensability of surgical cleaning brushes through microbiological studies that demonstrated that there was no significant change with the use of this artifact and without it. In addition, it is important to highlight, as a limitation of the study, the precariousness of articles in the area that cover the topic addressed, highlighting the need to implement new studies that address the issue in focus.